Detrimental Impact of Na Upon Rb Postdeposition Treatments of Cu(In, Ga)Se2 Absorber Layers. Issue 9 (9th September 2021) - de Wild, Jessica; Birant, Gizem; Thiruvallur Eachambadi, Raghavendran; Kohl, Thierry; Buldu, Dilara G.; Brammertz, Guy; Manca, Jean V.; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Abstract : Postdeposition Treatment In article number 2100390, Jessica de Wild and co‐workers performed a RbF postdeposition treatment on AlOx back‐passivated Cu(In, Ga)Se2 solar cells. It is found that Na present at the AlOx /Mo back contact inhibits Rb diffusion into the absorber layer. A detrimental redistribution of the alkali follows, leading to an injection barrier at the front and reduction of the acceptor concentration in the bulk.